Filsafat Idealisme dalam Pendidikan - Nurmalina, Nurmalina; Wahab, Muhbib Abdul (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Idealism philosophy emphasizes the importance of the mind, soul, or spirit over material or material things. The essence of humans is their soul or spirit, which is called "mind". Reason is the form that is able to manifest its world, and even become the driver of human behavior. The role of philosophy in the world of education is to provide guidance for the field of philosophy of education in order to realize the educational goals expected by a society or nation. So, the focus of this research is to analyze the role of Idealism Philosophy and its implementation in education. The literature research method is used to strengthen the research results. The writing technique in this paper begins with searching for various information from various sources such as books, articles, newspapers, and other relevant internet sources, then filtered to find the most suitable sources for the theme to be discussed. The conclusions drawn become a relevant whole unit with the theme being carried.